Bio-active compounds and antioxidant activity in flowers and seeds of Sunn hemp - Pimratch, Sumran; Thammapat, Pornpisanu; Mungkunkamchao, Tantika (วารสารเกษตรพระวรุณ มหาวิทยาลัยราชภัฏมหาสารคาม, 2022)
Sunn hemp (Crotalaria juncea) is generally used as green manure in agriculture because of its ability to fix nitrogen. It also has potential to be used as food and feed. The objectives of this study were to evaluate phytosterols, vitamin E, phenolic compounds and antioxidant activity in flower and seed and quantify fatty acid composition of Sunn hemp oil. Flower and seed of Sunn hemp had the phytosterols of 1,217.54 mg/100g and 1,283.82 mg/100g, respectively. β-sitosterol, campesterol and Δ5-stigmasterol constituted the major components of total phytosterols in both flower and seed. Vitamin E in seed (129.33 mg/100g) was higher than in flower (56.61 mg/100g), and the major components of total vitamin E were similar, consisting of α-tocopherol and γ-tocopherol. Total phenolic compound in flower (111.84 mgGAE/100g) was higher than in seed (80.44 mgGAE/100g), but antioxidant activity in seed (64.67 %) was higher than in flower (52.33 %). Sunn hemp oil had high unsaturated fatty acids of 68.90 %. Linolenic acid constituted 57.8 % of total fatty acids followed by palmitic acid (15.3 %) and stearic acid (11.5 %). The information is important for utilization of Sunn hemp as food and feed.